INOVASI MANAJEMEN KEUANGAN MELALUI KEGIATAN KEWIRAUSAHAAN (EDUPRENEURSHIP) SEBAGAI UPAYA PENINGKATAN MUTU PEMBELAJARAN DI MI - Suhermi, Lulut; Salim, Muhlisin; Bambang, Bambang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Financial limitations are often the main obstacle in improving the quality of learning in Islamic Elementary Schools (MI). Funding from the government and parental contributions (SPP) are often insufficient to finance innovative infrastructure and learning programs. This study aims to analyze how financial management innovation through entrepreneurial activities (edupreneurship) can contribute to improving the quality of learning in MI. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies at MI Al-Ikhlas as the research locus. Data were analyzed interactively through data reduction, data presentation, and drawing conclusions. The research findings show that: (1) The implementation of edupreneurship through the